Toward a new paradigm for urban mobility in Brazil: An empirical investigation in the city of Florianópolis. Issue 4 (31st March 2023) - Lanzini, Pietro; Pinheiro, Daniel; Jara, Eduardo
Abstract: Traffic congestion and unsustainable mobility patterns represent a severe issue for most Brazilian cities, with traditional approaches often proving to be scarcely effective in tackling the problem. We argue that a crucial hindrance is represented by the limited attention devoted to "the commuter perspective": only a deeper understanding of the motives behind mobility-related behaviors of citizens would enable policy makers to implement sound mobility plans. We performed an empirical investigation on residents of the city of Florianópolis (n = 436), analyzing the determinants of modal choice. Results confirm the pivotal role exerted by habits, and the willingness of respondents to opt for sustainable transport modes; a peculiar finding is represented by the marginality of social and environmental aspects in shaping commuters' behaviors, and the perceived lack of convenient alternatives that is yet hindering a broad shift which is seen as necessary. Based on the evidence emerging from the study, we provide a contribution to the debate by discussing possible lines of action and policy options that could be implemented.